An introduction to theory and reasoning in nursing - Johnson, Betty M.; Webber, Pamela Bayliss (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2015)
Theory and reasoning in nursing focuses on helping to develop the strong reasoning skills necessary for competent and caring practice, the fourth edition demonstrates the interconnections between theory, reasearch, and practice. The authors help you understand theory--what it is, how it supports nurses and their practice, and how they can use it to answer clinical questions and care for patients more effectively.
An introduction -- Language, meanings, structure, and relationships -- Theory, research, and reasoning -- Reasoning and technology -- Support theory -- Foundations of nursing theory -- Nursing theory -- Theory evaluation -- Introduction to research -- Theory and practice -- Multidisciplinary theory -- The future.
Includes bibliographical references and index.
Keywords: Nursing theory; Philosophy, Nursing